2016
DOI: 10.1038/ncomms12460
|View full text |Cite|
|
Sign up to set email alerts
|

Crowdsourced assessment of common genetic contribution to predicting anti-TNF treatment response in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) affects millions world-wide. While anti-TNF treatment is widely used to reduce disease progression, treatment fails in ∼one-third of patients. No biomarker currently exists that identifies non-responders before treatment. A rigorous community-based assessment of the utility of SNP data for predicting anti-TNF treatment efficacy in RA patients was performed in the context of a DREAM Challenge (http://www.synapse.org/RA_Challenge). An open challenge framework enabled the comparative eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 47 publications
4
68
0
Order By: Relevance
“…We showed that the SNP data contribute very little information to the prediction achieved using clinical covariates only, in accord with previous studies of cardiovascular disease (Morris et al, 2016) as well as of treatment response in RA (Sieberts et al, 2016). We showed that the SNP data contribute very little information to the prediction achieved using clinical covariates only, in accord with previous studies of cardiovascular disease (Morris et al, 2016) as well as of treatment response in RA (Sieberts et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We showed that the SNP data contribute very little information to the prediction achieved using clinical covariates only, in accord with previous studies of cardiovascular disease (Morris et al, 2016) as well as of treatment response in RA (Sieberts et al, 2016). We showed that the SNP data contribute very little information to the prediction achieved using clinical covariates only, in accord with previous studies of cardiovascular disease (Morris et al, 2016) as well as of treatment response in RA (Sieberts et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…All three methods achieved a (reasonable) identical prediction accuracy as measured by the correlation (0.44), the slope (0.98) and the PMSE (1.27; Supporting Information Figure 4). This indicates that most of the information about prediction comes from the nongenetic predictors, supporting the conclusions (in relation to prediction of change in DAS28) from a previous anti-TNF study (Sieberts et al, 2016).…”
Section: Prediction Based On Snps and Covariatessupporting
confidence: 81%
“…Candidate genes encoding proteins involved in the immune response have been fairly investigated to search for a possible association with TNF-i response in several autoimmune diseases, including RA [3336]. However, validated genomic biomarkers currently do not significantly allow the identification of non-responders before treatment in RA [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RA disease duration, disease activity, functional status, presence of autoantibodies [rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA)], and previous therapies can influence drug response [811]. Genetic inter-individual variability can also contribute to the differences in the response to treatment: some single nucleotide polymorphisms (SNPs) showed an association with bDMARDs response and might be useful for prediction, although few associations have been replicated [1215]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation